Pro-neurotensin depends on renal function and is related to all-cause mortality in chronic kidney disease. Issue 3 (September 2020) - Tönjes, Anke; Hoffmann, Annett; Kralisch, Susan; Qureshi, Abdul Rashid; Klöting, Nora; Scholz, Markus; Schleinitz, Dorit; Bachmann, Anette; Kratzsch, Jürgen; Nowicki, Marcin; Paeschke, Sabine; Wirkner, Kerstin; et al.
Abstract : Background: : Patients with chronic kidney disease (CKD) have a high risk of premature cardiovascular diseases (CVD) and show increased mortality. Pro-neurotensin (Pro-NT) was associated with metabolic diseases and predicted incident CVD and mortality. However, Pro-NT regulation in CKD and its potential role linking CKD and mortality have not been investigated, so far. Methods: : In a central lab, circulating Pro-NT was quantified in three independent cohorts comprising 4715 participants (cohort 1: patients with CKD; cohort 2: general population study; and cohort 3: non-diabetic population study). Urinary Pro-NT was assessed in part of the patients from cohort 1. In a 4th independent cohort, serum Pro-NT was further related to mortality in patients with advanced CKD. Tissue-specific Nts expression was further investigated in two mouse models of diabetic CKD and compared to non-diabetic control mice. Results: : Pro-NT significantly increased with deteriorating renal function ( P < 0.001). In meta-analysis of cohorts 1–3, Pro-NT was significantly and independently associated with estimated glomerular filtration rate ( P ≤ 0.002). Patients in the middle/high Pro-NT tertiles at baseline had a higher all-cause mortality compared to the low Pro-NT tertile (Hazard ratio: 2.11, P = 0.046). Mice with severe diabetic CKD did not show increased Nts mRNA expression in different tissues compared to control animals. Conclusions: : Circulating Pro-NT is associated with impaired renal function in independent cohorts comprising 4715 subjects and is related to all-cause mortality in patients with end-stage kidney disease. Our human and rodent data are in accordance with the hypotheses that Pro-NT is eliminated by the kidneys and could potentially contribute to increased mortality observed in patients with CKD.